Biological cells in the speciation analysis of heavy metals. Issue 47 (11th November 2016) - Yang, Ting; Wang, Xiao-Yan; Wang, Li-Yun; Chen, Ming-Li; Wang, Jian-Hua
Abstract : Biological cells are versatile in both metal remediation and metal preconcentration and speciation. Abstract : Biological cells are versatile attributed to their extensive applications in metal remediation as well as metal preconcentration and speciation. Their capability to distinguish metal species based on the toxicity difference endows them with incomparable superiority over synthetic adsorbents as solid phase extraction (SPE) media for heavy metal speciation besides their intrinsic advantages of low cost, wide range of sources, abundant binding sites and environmental friendly feature. In this review, we provide an overview on the development of biological cell-based non-chromatographic heavy metal speciation, focusing on the recent achievement during the last decade. The main speciation strategies proposed in the reported studies as well as the advantages and drawbacks are discussed. We further outline the metal uptake mechanisms and key issues in biosorption and bioaccumulation. Future perspectives and challenges in this field are depicted.